Capital Account Liberalization and Corporate Taxes - Lockwood, Ben (IMF Working Papers; Working Paper ;, 2003)
This paper studies whether exchange controls, particularly on the capital account, affect the choice of corporate tax rates, using a panel of 21 OECD countries over the period 1983-99. It builds on existing literature by (1) using a unique dataset with several different measures of the corporate tax rate calculated from the actual parameters of the tax systems, and (2i) allowing exchange controls to affect the intensity of strategic interaction between countries in setting taxes, as well as the levels of tax they choose. We find some evidence that (1) the level of a country's tax, other things equal, is lowered by a unilateral liberalization of exchange controls; and (2) that strategic interaction in taxsetting between countries is increased by liberalization. These effects are stronger if the country is a high-tax one and if the tax is the statutory or effective average one. There is also evidence that countries' own tax rates are reduced by liberalization of exchange controls in other countries.